Development of technology for cultivation of of high-processing stones of Chlorella vulgaris in low temperature conditions - Прокофьєва, М. А.; Семенов, М. І.; Степневська, Я. В.; Сметанін, В. Т. (Problems of Environmental Biotechnology, 2018)
Chlorella vulgaris strain was selected for cultivation under low temperature conditions and different approaches to the accumulation of microalgae biomass were studied. Optimal conditions for its cultivation, concentration and disintegration of cells were selected and justified. The efficiency of using biomass in the sewage treatment system of poultry complexes and as a component of the methane substrate of the biogas complex is shown.